Analisis Pengaruh Kualitas Layanan Website Pembinaan Sekolah Menengah Kejuruan (PSMK) Terhadap Kepuasan Pengguna Dengan Menggunakan Metode Webqual - Iis Istiqomah; Okta Irawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to evaluate the factors influencing the quality of the Pembinaan Sekolah Menengah Kejuruan (PSMK) website using a user satisfaction approach. The PSMK website is a critical component of the Education Management Information System; however, users often encounter issues related to information quality, ease of interaction, usability, and interface design. These challenges may hinder the effectiveness of technology-based educational services. As a solution, this study employs the Modified WebQual 4.0 method to analyze four key aspects: information quality, interaction, usability, and interface design. Data were collected through a survey of 100 PSMK website users and analyzed using multiple linear regression. This approach helps identify the most significant factors influencing user satisfaction. The results indicate that all four factors—information quality, interaction, usability, and interface design—positively and significantly affect user satisfaction. Enhancing these aspects can significantly improve the user experience. These findings provide valuable insights for educators and policymakers to improve the quality of the PSMK website, support more effective educational services, and promote the integration of technology in vocational education. By addressing these factors, the PSMK website can better support the achievement of educational goals at the vocational school level.